Effect of pH and medium composition on chain elongation with Megasphaera hexanoica producing C4-C8 fatty acids - Fernández-Blanco, Carla; Veiga, María C.; Kennes, Christian (Frontiers in Microbiology, 2023)
Introduction Chain elongation technology, which involves fermentation with anaerobic bacteria, has gained attention for converting short and medium chain substrates into valuable and longer-chain products like medium chain fatty acids (MCFAs). In the recent past, the focus of studies with pure chain elongating cultures was on species of other genera, mainly Clostridium kluyveri. Recently, other chain elongators have been isolated that deserve further research, such as Megasphaera hexanoica. Methods In this study, batch studies were performed in bottles with two different media to establish the optimal conditions for growth of M. hexanoica: (a) a medium rich in different sources of nitrogen and (b) a medium whose only source of nitrogen is yeast extract. Also, batch bioreactor studies at pH values of 5.8, 6.5 and 7.2 were set up to study the fermentation of lactate (i.e., electron donor) and acetate (i.e., electron acceptor) by M. hexanoica. Results and discussion Batch bottle studies revealed the yeast extract (YE) containing medium as the most promising in terms of production/cost ratio, producing n-caproate rapidly up to 2.62 ± 0.24 g/L. Subsequent bioreactor experiments at pH 5.8, 6.5, and 7.2 confirmed consistent production profiles, yielding C4-C8 fatty acids. A fourth bioreactor experiment at pH 6.5 and doubling both lactate and acetate concentrations enhanced MCFA production, resulting in 3.7 g/L n-caproate and 1.5 g/L n-caprylate. H2 and CO2 production was observed in all fermentations, being especially high under the increased substrate conditions. Overall, this study provides insights into M. hexanoica’s behavior in lactate-based chain elongation and highlights optimization potential for improved productivity.